Sequence-specific DNA binding agents - Waring, Michael J. (RSC biomolecular sciences., 2006)
The binding of antibiotics and drugs to DNA is a fast developing area of research with important applications in medicine, particularly the treatment of cancer. Sequence-specific DNA Binding Agents uniquely discusses key aspects of this topic, providing a novel perspective on the subject. Written by experts in the field, this book discusses diverse modes of binding of antibiotics and drugs to DNA, emphasising matters that are important or promising for cancer treatment. Chapters discuss established agents like actinomycin D but also look at novel drugs with strong potential in chemotherapy suc.